Policy of notary deed in Indonesia, Netherland, and Belgium during the Covid-19 pandemic - Maghfira Humaira; Pieter Everhardus Latumeten (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
This study aims to compare the making of a notary deed during the Covid-19 period in Indonesia, the Netherlands and Belgium. Normative juridical law research is the method employed in this research. Analytical descriptive was further also utilized, while the data collection technique used is literature study. The results of the study indicated the importance of changes to Law Number 30 of 2004 concerning Notary Positions as amended by Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notary Positions (